Reduced glutamate in white matter of male neonates exposed to alcohol in utero: a (1)H-magnetic resonance spectroscopy study - Howells, F. M. (Metab Brain Dis, 2016)
In utero exposure to alcohol leads to a spectrum of fetal alcohol related disorders (FASD). However, few studies used have used proton magnetic resonance spectroscopy ((1)H-MRS) to understand how neurochemical disturbances relate to the pathophysiology of FASD. Further, no studies to date have assessed brain metabolites in infants exposed to alcohol in utero. We hypothesize that neonates exposed to alcohol in utero will show decreased glutamatergic activity, pre-emptive of their clinical diagnosis or behavioural phenotype. Single voxel (1)H-MRS data, sampled in parietal white and gray matter, were acquired from 36 neonates exposed to alcohol in utero, and 31 control unexposed healthy neonates, in their 2nd-4th week of life. Metabolites relative to creatine with phosophocreatine and metabolites absolute concentrations using a water reference are reported. Male infants exposed to alcohol in utero were found to have reduced concentration of glutamate with glutamine (Glx) in their parietal white matter (PWM), compared to healthy male infants (p = 0.02). Further, male infants exposed to alcohol in utero had reduced concentration and ratio for glutamate (Glu) in their PWM (p = 0.02), compared to healthy male infants and female infants exposed to alcohol in utero. Female infants showed higher relative Glx and Glu ratios for parietal gray matter (PGM, p < 0.01), compared to male infants. We speculate that the decreased Glx and Glu concentrations in PWM are a result of delayed oligoden-drocyte maturation, which may be a result of dysfunctional thyroid hormone activity in males exposed to alcohol in utero. Further study is required to elucidate the relationship between Glx and Glu, thyroid hormone activity, and oligodendrocyte maturation in infants exposure to alcohol in utero.